Disability Measurement in Household Surveys : A Guidebook for Designing Household Survey Questionnaires - Tiberti, Marco (World Bank, Washington, DC, 2020)
An estimated one billion people worldwide live with disabilities. Of the world’s poorest people, one in five live with disabilities, in conditions where they lack material resources as well as opportunities to exercise power, reach their full potential, and flourish in various aspects of life. These numbers are rising particularly quickly in high-income countries, where national populations are growing older at unprecedented rates, leading to a higher incidence of diabetes, cardiovascular diseases, and mental disorders. To ensure disability-inclusive development, disability data must capture the degree to which society is inclusive in all aspects of work, school, family, transportation, and civic participation, inter alia. Disaggregating disability indicators will allow us to understand the quality of life of people with disabilities, towards developing programs and policies to address existing disparities. To facilitate the World Bank’s commitment to disability-inclusive development, this guidebook supports the implementation of the Washington Group Short Set (WG-SS) in multi-topic household surveys, towards improving the collection of disaggregated disability data. The first section presents an overview of definitions of disability from the sociopsychological literature in order to explore how disability is defined and who is considered disabled. The second section looks at three different methods for disability measurement in multi-topic household survey. The final section presents the functioning disability module that comprises the six core WG-SS functional domains (seeing, hearing, walking, cognition, selfcare, and communication), to be administered to household members above five years of age.